Features of Skin Cancer in Black Individuals: A Single-Institution Retrospective Cohort Study - Manci, Rachel; Dauscher, Megan; Marchetti, Michael A.; Usatine, Richard; Rotemberg, Veronica; Dusza, Stephen; Marghoob, Ashfaq (Dermatology Practical & Conceptual, 2022)
Background: Minimal knowledge exists regarding skin cancers in Black individuals, which may adversely affect patient care.Objectives: To describe clinical features and risk factors of skin cancers in Black individuals. Methods: Retrospective study of Black individuals diagnosed with skin cancer between January 2000 and January 2020 at our institution.Results: 38,589 patients were diagnosed with skin cancer, of which 165 were Black. One-hundred-thirteen of these Black individuals were diagnosed with melanoma, 35 with squamous cell carcinoma (SCC), and 17 with basal cell carcinoma (BCC). Most melanomas (80.0%, n=90) were of the acral subtype; 75% (6 of 8 cases with dermoscopic images) displayed a parallel ridge pattern (PRP). The surrounding uninvolved background skin was visible in 7 cases, all demonstrating a PRP. This disappeared adjacent to most of the melanoma lesions (n=4, 57.1%) – creating a peripheral hypopigmented “halo”. The nonmelanoma skin cancers were pigmented and had similar dermoscopic features as reported in predominantly white populations. Most SCCs (n=5, 71.4%) had a hypopigmented “halo” and most BCCs (n=10, 55.6%) had an accentuated reticular network adjacent to the lesions. Most (80.0%, n=28) SCC patients had a chronic inflammatory condition. Two BCC patients (16.7%) had Gorlin syndrome.Conclusions: Skin cancers are pigmented in Black individuals. In both ALMs and SCCs, we noted a peripheral rim of hypopigmentation between the lesions and the surrounding uninvolved background skin, while BCCs had accentuation of the background pigmentation adjacent to the lesions. Most acral melanomas displayed a PRP, which was also seen in surrounding uninvolved background skin.